Solvent-free catalytic synthesis and optical properties of super-hard phase ultrafine carbon nitride nanowires with abundant surface active sites. Issue 28 (29th February 2016) - Wang, Jilin; Zhang, Lulu; Long, Fei; Wang, Weimin; Gu, Yunle; Mo, Shuyi; Zou, Zhengguang; Fu, Zhengyi
Abstract : Hot-melt reduction solvent-free catalytic synthesis and optical property of ultrafine α/β-C3 N4 nanowires with abundant surface active sites. Abstract : High-quality ultrafine α/β-carbon nitride (α/β-C3 N4 ) nanowires have been fabricated through a novel hot melt reduction synthetic method using polyvinylchloride ([–C2 H3 Cl–] n ), ammonium chloride (NH4 Cl) and ferric oxide (Fe2 O3 ) as raw materials. The purity, structure, morphology, crystallinity and surface state of the as-prepared samples were investigated by FSEM, TEM, HRTEM, SAED, XRD, EDX, FTIR and XPS. The nanowires presented good crystallinity with a length range of 1–4 μm and an average diameter of about 10 nm. Every nanowire possessed a high specific surface area and rough surface with abundant exposed atoms/prominences, indicating that the surface structure will facilitate further surface modification, functionalization and related applications. In addition, UV-vis diffuse reflectance and the corresponding photoluminescence (PL) spectra indicated that the nanowires have a wide band gap (4.38 eV) and obvious ultraviolet luminescence properties at the maximum emission peak of about 340 nm. A catalytic reaction mechanism and the growth model were also proposed to explain the formation process of the C3 N4 nanowires.